The Pengaruh Kesehatan Mental dan Dukungan Orang Tua terhadap Indeks Prestasi Kumulatif Mahasiswa Preklinik Mahasiswa Fakultas Kedokteran Gigi Universitas YARSI - Aldila Khanza Carbelani; Nur Hidayati Nosi Prastiyani; Agus Ardinansyah (Lembaga Penelitian Universitas YARSI, 2026)
Background: High academic pressure among dental students is often associated with mental health conditions that are presumed to play a role in academic achievement. Parental support is also presumed to contribute to academic achievement; therefore, the relationship among these factors still needs to be further investigated. Objective: This study aimed to determine the effect of mental health and parental support on grade point average (GPA) among preclinical students of the Faculty of Dentistry, YARSI University. Methods: This study was a quantitative analytic study with a cross-sectional design involving 119 preclinical students. Data were collected using the Depression Anxiety Stress Scales 21 (DASS-21) questionnaire and a parental support questionnaire developed by the researcher and distributed via Google Forms. GPA data were obtained from the academic office of the Faculty of Dentistry, YARSI University. Data analysis was performed using the Spearman correlation test. Results: The results showed a significant relationship between depression and students’ GPA (p = 0.022; r = −0.210) as well as between anxiety and students’ GPA (p = 0.025; r = −0.205), with a negative direction and weak strength of correlation. The stress variable (p = 0.113; r = −0.146) and parental support (p = 0.149; r = 0.133) did not show a significant relationship with students’ GPA. Discussion: The negative relationship between depression and anxiety indicates that mental health can affect students’ academic achievement. These conditions may disrupt cognitive function and reduce learning motivation, thereby affecting students’ ability to optimally participate in the learning process. Conclusion: There is a significant effect of depression and anxiety, while there is no significant effect of stress and parental support on the GPA of preclinical students at the Faculty of Dentistry, YARSI University.